2014
DOI: 10.1167/iovs.13-13546
|View full text |Cite
|
Sign up to set email alerts
|

Serine Protease Inhibitor A3K Suppressed the Formation of Ocular Surface Squamous Metaplasia in a Mouse Model of Experimental Dry Eye

Abstract: Topical application of SERPINA3K ameliorated the severity of ocular surface squamous metaplasia and suppressed the formation of BAC-induced dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Given the fact that epithelial cell hyperplasia was observed in the saline- but not the α-MSH-treated dry eye corneas ( Fig. 4 ), the α-MSH’s promotion on cell proliferation appears unlikely, although Ki67 or 5-Bromo-2´-Deoxyuridine staining is needed to exclude this possibility 40 . Therefore, TUNEL staining was performed to examine the effects of α-MSH on apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…Given the fact that epithelial cell hyperplasia was observed in the saline- but not the α-MSH-treated dry eye corneas ( Fig. 4 ), the α-MSH’s promotion on cell proliferation appears unlikely, although Ki67 or 5-Bromo-2´-Deoxyuridine staining is needed to exclude this possibility 40 . Therefore, TUNEL staining was performed to examine the effects of α-MSH on apoptosis.…”
Section: Discussionmentioning
confidence: 96%
“…2 Abnormal differentiation is an important feature of squamous metaplasia, which causes the pathological transition of a nonkeratinized, stratified epithelium into a nonsecretory, keratinized epithelium. 1,24,48 The emergence of epidermisspecific K10 protein, a lower level of Pax6 expression and goblet cell loss indicates that the epithelium has lost its secretory function and has been replaced by squamous epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Many ocular surface diseases such as dry eye, Stevens-Johnson syndrome, mucous membrane pemphigoid, chemical/thermal burns, pterygium, and vitamin A deficiency often show chronic inflammation of the ocular surface. [3][4][5][6] Chronic inflammation can lead to squamous metaplasia of the ocular surface epithelium through a signaling pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, activation of PAR2 by serine proteases plays an important role in innate and inflammatory responses of corneal infection and inflammation 25 . It has been reported that the serine protease inhibitor A3K has promising experimental in vivo results in a mouse and rabbit model for dry eye 29,49 . In addition, KLK13 has also recently been discovered as a potential target for DES 11 .…”
Section: Discussionmentioning
confidence: 99%